Anterior Teeth Splinting After Orthodontic Treatment: 3D Analysis Using Finite Element Method. - A Geramy; J M Retrouvey; F Sobuti; H Salehi (Tehran University of Medical Sciences, 2012)
Retention after orthodontic treatment is still an important part of the treatment. Splints are considered as an alternative for removable retainers. The main goal of this study was to assess splinting biomechanically.Three dimensional finite element models (3D) were designed of a mandibular anterior segment which included six anterior teeth with their supporting tissues (model 1 as control) and with a bonded lingual fixed retainer in the two other models. The wire cross section was round (0.016") in model 2 and rectangular (0.016" × 0.022") in model 3. The models were designed in Solid Works 2006 and analyzed in ANSYS Workbench Ver. 11.0 SolidWorks Incisors were loaded with a vertical force of 187 N. PDL stress and tooth displacements were evaluated.The numeric findings showed an increase after splinting in the central incisors [2.42 MPa to 4.57 MPa (round) and 16.66 (rectangular) MPa] in biting with four incisors. Biting with two incisors decreased the stress after splinting [2.42 MPa to 1.7 MPa (round wire) and 1.77 MPa (rectangular wire)]. In lateral movement, all teeth showed an increased stress except for the working side canine.Splinted cases (with round or rectangular wires) can benefit from stress redistribution when biting small food particles and in lateral movement.